PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, UKURAN PERUSAHAAN, LIKUIDITAS, DAN PERTUMBUHAN ASET TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI 2014-2016) - Novita Suryaningsih, 14.05.52.0110; Nurhayati, Ida (Students Journal of Accounting and Banking, 2018)
The purpose of this study to test the effect of disclosure of corporate social responsibility (CSR), leverage, size, liquidity and asset growth to profitability on manufacturing companies listed in Indonesia Stock Exchange 2014-2016. Data used in this research is secondary data,the data in this study were obtained from the Anuat Report (AR) 2014-2016. This study was conducted using a sample of 235 companies listed on the stock exchange in 2011-2015. Methods of sample selection using purposive sampling and analysis model used is multiple linear regression. The result of the research shows that disclosure of corporate social responsibility (CSR) variable has positive and significant influence to the profitability (ROA), whereas leverage (DER) variable has negative and significant influence to the profitability (ROA), whereas size variable has positive and significant influence to the profitability (ROA), whereas liquidity (CR) variable has positive and significant influence to the profitability (ROA), and turnover Assets effect on profitability because of the significant value of the variable that is more than 0.05 and variable has positive.Keywords: Disclosure of Corporate Social Responsibility, leverage, firm size, liquidity, and profitability